(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Medical images are generated and transmitted between hospitals for analysis by physicians who are geographically apart. Moreover, as the patient data is also embedded within the medical images, it is very important to maintain the privacy of patient data. For data hiding in images, many techniques are used. Some techniques will hide data but embedding cause some misrepresentation of image, and some techniques will cause misrepresentation during retrieval. In this paper, new approach of data hiding technique is proposed to hide the data in both Region of Interest (ROI) of medical images and Non Region of Interest (NROI) of medical images and recover the data as well. Medical image and hidden data are recoverable without any loss of data. Keywords: Data hiding, Medical images, ROI, NROI, LSB